1999
DOI: 10.3354/meps189195
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional condition of female Calanus euxinus from cyclonic and anticyclonic regions of the Black Sea

Abstract: ABSTRACT-The content and composition oi lipids in Calanus euxinus females were studied in cyclonic and anticyclonic regions in the southern Black Sea during the period of persistent density stratification (September 1996). The lipid content of C. euxinus from cyclonic regions was greater than of individuals from anticyclonic regions (average 101.9 and 58.8 pg ind.-l, respectively). Total lipid content (mainly wax esters, 70 to 72 %, and triacylglycerols, 8 to 13 %) of female C. euxinus was correlated with chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…During all seasons, C. euxinus is able to accumulate large amounts of lipids (especially wax esters) in the body (Yuneva et al, 1997(Yuneva et al, , 1999. In the present study, during the sampling period, C. euxinus contained the highest amount of total lipids in February (7.03%) and the lowest in September (3.02%).…”
Section: Fatty Acid Profilesupporting
confidence: 52%
See 2 more Smart Citations
“…During all seasons, C. euxinus is able to accumulate large amounts of lipids (especially wax esters) in the body (Yuneva et al, 1997(Yuneva et al, , 1999. In the present study, during the sampling period, C. euxinus contained the highest amount of total lipids in February (7.03%) and the lowest in September (3.02%).…”
Section: Fatty Acid Profilesupporting
confidence: 52%
“…The average amount of total lipids of C. euxinus was 14.1±6.0% at a different station at the South-eastern Black Sea and this proportion decreased to 7.7±5.1% in female C. euxinus living in deeper waters, as reported by Svetlich et al (2006). Yuneva et al (1999) reported on total lipids of female C. euxinus at the Southern Black Sea (September 1996) and indicated that the average amount of total lipids of C. euxinus in cyclonic regions (101.9 µgind -1 ) was greater than that from anticyclonic regions (58.8 µg ind -1 ). It was pointed out that lipid content (wax esters, triacylglycerols) of female C. euxinus was correlated with chl-a (r 2 =0.92, p<0.05).…”
Section: Fatty Acid Profilementioning
confidence: 99%
See 1 more Smart Citation
“…To determine the proportion of TAGs in TLs, the lipid extract aliquots were separated into fractions by one-dimensional thin layer chromatography (TLC) on Silufoll UW254 plates in a mixture of solvents with different polarity (Yuneva et al, 1999). Chromatograms were developed by heating in a thermostat at 110°C for 5-7 min.…”
Section: Methodsmentioning
confidence: 99%
“…This variability is related to the degree of preparedness for migration, caused by different food supply. The same influence of food supply is seen by comparing the main energy substrates: total lipid content of copepod Calanus euxinus and glycogen content of ctenophora Pleurobrachia rhodopis were different in cyclonic and anticyclonic zones (Yuneva et al, 1999).…”
Section: Discussionmentioning
confidence: 78%